Care-giving children having Down syndrome - life impacts and psycho-social experiences of mothers - Chan, K.G (2017)
This paper highlights the life impacts and psycho-social experiences of mothers care giving their children having Down syndrome in the Malaysian state of Sarawak. Methods: In-depth interviews were conducted with 26 participants who were accessed from selected health clinics, schools and community–based rehabilitation centres using a purposive sampling procedure. Findings: Bringing up children having Down syndrome had impacted upon mothers to some extent in term of their family functioning, increased competence in childcare and motivation to reach out to others. Psychosocially, mothers experienced a range of difficult emotions, feeling unsupported, worries and concerns, including their concern about recurrence Down syndrome. Integral to their experience was the excitement and joy with child’s progress. Conclusion: Insights as gained from the main findings indicate that care-giving children having Down syndrome did have some life impacts upon mothers. However, their experiences are not all negative though some of their psychosocial-related experiences are of concern. It augurs well for nurses as care professionals to be needs-sensitive and to provide timely supportive nursing care to facilitate the mental well-being of mothers and an environment helpful for the optimal development of their children.